Ventricular tachycardia in ischemic cardiomyopathy; a combined endo-epicardial ablation as the first procedure versus a stepwise approach (EPILOGUE) – study protocol for a randomized controlled trial. Issue 1 (December 2015) - Hendriks, Astrid; Khan, Muchtiar; Geller, Laszlo; Kardos, Attila; de Vries, Lennart; Yap, Sing-Chien; Wijchers, Sip; Theuns, Dominic; Szili-Torok, Tamas
Abstract Background The role of epicardial substrate ablation of ventricular tachycardia (VT) as a first-line approach in patients with ischemic heart disease is not clearly defined. Epicardial ablation as a first-line option is standard for patients with nonischemic dilated cardiomyopathy and arrhythmogenic right ventricular cardiomyopathy. Several nonrandomized studies, including studies on patients with ischemic heart disease, have shown that epicardial VT ablation improves outcome but this approach was often used after a failed endocardial approach. The aim of this study is to determine whether a combined endo-epicardial scar homogenization as a first-line approach will improve the outcome of VT ablation. Methods/Design The EPILOGUE study is a multicenter, two-armed, nonblinded, randomized controlled trial. Patients with ischemic heart disease who are referred for VT ablation will be randomly assigned to combined endo-epicardial scar homogenization or endocardial scar homogenization only (control group). The primary outcome is recurrence of sustained VT during a 2-year follow-up. Secondary outcomes include procedural success and safety. Discussion This study is the first randomized trial that evaluates the role of a combined endo-epicardial scar homogenization versus endocardial scar homogenization for the treatment of ischemic scar-related VT. Trial registration NL4816807814v02